# How do you solve 2( - 6x + 9) = - 66?

Nov 28, 2016

$x = 7$

#### Explanation:

$2 \left(- 6 x + 9\right) = - 66$

First distribute the 2 to $- 6 x \mathmr{and} 9$

$- 12 x + 18 = - 66$

Then Subtract $18$ from both sides

$- 12 x = - 84$

And lastly, divide by $- 12$

$x = 7$

Nov 28, 2016

$x = 7$

#### Explanation:

$1.$ First, distribute the $2$ into the $\left(- 6 x + 9\right)$ by first multiplying the $2$ by $- 6 x$ and then by $9$ to get $- 12 x + 18$

$- 12 x + 18 = - 66$

$2.$ Then, since $18$ does not have an $x$ with it, you can subtract 18 from both sides of the equation, taking away the $18$ from the left side and subtracting $18$ from $- 66$ as well.

This makes sure that both sides of the equals sign are equal. When you solve equations like this, always try to look for ways to get the $x$ term alone on one side. So, by doing this step, you have

$- 12 x = - 84$

$3.$ Look for ways to isolate $x$ again. This is an easy one since $x$ is just multiplied by $- 12$. Divide both sides by $- 12$ to get $x = 7$.

$\frac{- 12 x}{- 12} = \frac{- 84}{- 12}$

$x = 7$

I hope this was helpful! :)